Économie verte et territoire : l’exemple nord-parisien - Boris Lebeau (Territoire en Mouvement)
This article analyses the position of eco-industries in the metropolitan dynamics, with the example of northern Paris metropolis. The focus is particularly on the complex relations that have developed between businesses and the 'communauté d'agglomération' Plaine Commune for more than ten years. The preservation or the reject of these activities are partly conditioned by these relations.